Від традицій до інновацій: сучасні тренди сталого розвитку за дослідженнями м'ясних виробів - Земелько, Марія Леонідівна; Бухкало, Світлана Іванівна; Ковальчук, Вікторія Миколаївна (Яроче́нко Я. В., 2025)
The influence of functional components on rheological, physicochemical and organoleptic characteristics of meat products is also established. The theoretical and methodological bases of the study were the provisions of general scientific methods of cognition and specific methods of assessing the quality of finished meat products and raw materials from which it is made. Theoretical eneralization, grouping and comparison was used to reveal the essence of the concept of "functional components". On the basis of comparison of theoretical knowledge and practical experiments, conclusions and proposals for improving production and improving the properties of meat products with functional components are made.
Keywords: м'ясопереробна промисловість; шкідливі компоненти; природні антиоксиданти; консерванти; функціональні добавки; м'ясні вироби; органолептичні властивості; зберігання